2017
DOI: 10.5194/acp-17-4355-2017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2000–2050 climate change on particulate matter in the United States: results from a new statistical model

Abstract: Abstract. We use a statistical model to investigate the effect of 2000–2050 climate change on fine particulate matter (PM2. 5) air quality across the contiguous United States. By applying observed relationships of PM2. 5 and meteorology to the IPCC Coupled Model Intercomparision Project Phase 5 (CMIP5) archives, we bypass some of the uncertainties inherent in chemistry-climate models. Our approach uses both the relationships between PM2. 5 and local meteorology as well as the synoptic circulation patterns, def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
95
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 60 publications
(90 reference statements)
4
95
0
5
Order By: Relevance
“…Tai et al (2012a) showed that cold fronts associated with midlatitude cyclone passages and maritime inflows were the major ventilation mechanisms of PM 2.5 in the US. Shen et al (2017) further showed that variability of PM 2.5 over the US explained by both local meteorology and synoptic factors (43%) are in average about 10% higher than solely using local 20 meteorology (34%). In Asia, Chen et al (2008) demonstrated that synoptic high-pressure systems in northern Mongolia associated with cold fronts facilitate the dispersion of air pollutants over northern China, whereas a surface high centered on BTH favors accumulation.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Tai et al (2012a) showed that cold fronts associated with midlatitude cyclone passages and maritime inflows were the major ventilation mechanisms of PM 2.5 in the US. Shen et al (2017) further showed that variability of PM 2.5 over the US explained by both local meteorology and synoptic factors (43%) are in average about 10% higher than solely using local 20 meteorology (34%). In Asia, Chen et al (2008) demonstrated that synoptic high-pressure systems in northern Mongolia associated with cold fronts facilitate the dispersion of air pollutants over northern China, whereas a surface high centered on BTH favors accumulation.…”
Section: Introductionmentioning
confidence: 94%
“…We finally construct a statistical model using annual median synoptic frequency and annual mean local meteorology to project 2000-2050 PM 2.5 changes, given present-day and future climate simulations by an ensemble of climate 10 models. This study represents an advancement over that of Tai et al (2012a, b) in terms of methodology by considering the joint effects of synoptic frequency and local meteorology, and is on a par with the work of Shen et al (2017), who focused on the US instead. Our work represents the first attempt to apply these methods to China air quality in an effort to derive a statistical projection of future PM 2.5 concentrations based on historical PM 2.5 -meteorology relationships.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations